Relationship Between Individual Factors And Environmental Factors Towards Eye Strain In Laptop Workers In Office Environments - Aditya Sukma Pawitra; Divanadya Pandu Pranata Putri; Dhian Novianthy; Khuliyah Candraning Diyanah (Jurnal EduHealth, 2025)
This study aims to analyze the influence of individual and environmental factors on eye fatigue among laptop users in office environments. The research was conducted using a descriptive observational design involving 33 workers at LMA Consortium Office, Kediri, East Java, with data collected through questionnaires, observations, and lighting intensity measurements. The findings reveal that most workers experienced eye fatigue, primarily due to laptop usage exceeding 4 hours per day, low lighting intensity (averaging 95.7 lux), and inadequate rest habits. Common complaints included blurred vision, eye discomfort, and headaches. Individual factors such as age, gender, and eyewear usage showed no significant relationship with eye fatigue, whereas environmental factors, particularly lighting, had a significant impact. Recommendations include improving lighting conditions, implementing ergonomic workplace practices, and raising worker awareness about the importance of eye rest. These findings emphasize the importance of ergonomic workplace management to reduce the risk of eye fatigue among laptop users.